Clinical manifestations and trend of dengue cases admitted in a tertiary care hospital, Udupi district, Karnataka - Kumar Ashwini; Rao Chythra; Pandit Vinay; Shetty Seema; Bammigatti Chanaveerappa; Samarasinghe Charmaine (Wolters Kluwer Medknow Publications, 2010)
Background: India is one of the seven identified countries in the South-East Asia region regularly reporting dengue fever (DF)/dengue hemorrhagic fever (DHF) outbreaks and may soon transform into a major niche for dengue infection in the future with more and more new areas being struck by dengue epidemics. Objective: To study the clinical manifestations, trend and outcome of all confirmed dengue cases admitted in a tertiary care hospital. Study Design: Record-based study conducted in a coastal district of Karnataka. Required data from all the laboratory confirmed cases from 2002 to 2008 were collected from Medical Records Department (MRD) and analyzed using SPSS 13.5 version. Results: Study included 466 patients. Majority were males, 301(64.6%) and in the and in the age group of 15-44 years, 267 (57.5%). Maximum number of cases were seen in 2007, 219 (47%) and in the month of September, 89 (19.1%). The most common presentation was fever 462 (99.1%), followed by myalgia 301 (64.6%), vomiting 222 (47.6%), headache 222 (47.6%) and abdominal pain 175 (37.6%). The most common hemorrhagic manifestation was petechiae 84 (67.2%). 391 (83.9%) cases presented with dengue fever, 41 (8.8%) dengue hemorrhagic fever, and 34 (7.3%) with dengue shock syndrome. Out of 66 (14.1%) patients who developed clinical complications, 22 (33.3%) had ARDS and 20 (30.3%) had pleural effusion. Deaths reported were 11(2.4%). Conclusion: Community awareness, early diagnosis and management and vector control measures need to be strengthened, during peri-monsoon period, in order to curb the increasing number of dengue cases.